Pelatihan Manajemen Keuangan dan Peningkatan Daya Saing Melalui Digital Marketing Bagi Pelaku Usaha Mikro di Desa Brangjan Kec.Ungaran Barat Kab.Semarang - Ida Ayu Gede.D.E.P; Made Konny Koswara; Yoki Nawan Gunara; Luluk Fiya Afiyati; Sekar Ayu Maharani (STIKES Columbia Asia Medan, 2023)
Micro-enterprises play an important role in the regional economy but often face obstacles in financial management and marketing strategies. A lack of understanding in financial management causes inefficiency in capital management, while minimal use of digital technology in marketing limits business competitiveness. This community service program aims to increase the capacity of micro-enterprises in Brangjan Village, West Ungaran District, Semarang Regency through financial management training and digital marketing strategies.The methods used in this program include socialization, training, and direct assistance in simple financial recording, working capital management, and the implementation of digital marketing strategies using social media and e-commerce platforms. The results of this activity show an increase in participants' understanding of financial management and their ability to implement digital marketing to expand market reach. With this training, it is hoped that micro-enterprises in Brangjan Village can develop further, become more competitive, and achieve long-term business sustainability.Additionally, the training on simple financial management provided participants with an understanding of transaction recording and the importance of cash flow in maintaining business operations. In terms of digital marketing, participants were trained to utilize social media and e-commerce platforms such as Instagram, Facebook, and Tokopedia to introduce their products to a wider market. Moving forward, it is hoped that participants will be able to leverage this knowledge to optimize their revenue and expand their customer base. This program also contributes to increasing digital and financial literacy for micro-entrepreneurs in the village. Overall, the training aims to create a more sustainable and efficient business ecosystem, which in turn can enhance the competitiveness of micro-enterprises at the local and regional levels.